1977
DOI: 10.1111/j.1600-0560.1977.tb00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Dyskeratosis in Morbus Darier

Abstract: Biospy specimens from three patients with morbus Darier were studied by electron microscopy: Grains appeared in groups in the midst of dyskeratotic lesions and were recognized as being the result of more advanced acantholysis and precocious keratinization. Corps ronds were formed individually in the regions lateral to that of grains, where hypergranulosis was prominent in contrast to a mild dyskeratosis. Therefore, the formation of grains and corps ronds seem to be independent of each other. While in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1
2

Year Published

1978
1978
2000
2000

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
1
6
1
2
Order By: Relevance
“…Many ultrastructural studies of Hailey-Hailey disease and Darier's disease have demonstrated detachment of tonofilaments from desmosomes (28,29) and splitting of desmosomes {30-33). Some authors have observed intracytoplasmic desmosomes (30,34). We found intracytoplasmic desmosomes in either disease so rarely that they can not account for the diffuse immunofluorescence of desmosomal components found in the cytoplasm in acanthoiytic cells.…”
Section: Discussioncontrasting
confidence: 57%
“…Many ultrastructural studies of Hailey-Hailey disease and Darier's disease have demonstrated detachment of tonofilaments from desmosomes (28,29) and splitting of desmosomes {30-33). Some authors have observed intracytoplasmic desmosomes (30,34). We found intracytoplasmic desmosomes in either disease so rarely that they can not account for the diffuse immunofluorescence of desmosomal components found in the cytoplasm in acanthoiytic cells.…”
Section: Discussioncontrasting
confidence: 57%
“…Disruption of desmosome–keratin filament complexes in keratinocytes on electron microscopy has been demonstrated in previous studies on lesional skin specimens from HHD and DD patients. 6–12 In both of these diseases, abnormal distributions of desmosomal proteins have been shown by immunohistochemistry and immunoelectron microscopy, although no apparent loss of expression has been detected. 13–22 These results suggest that abnormalities in cell adhesion structures, including desmosomes and adherens junctions, result in a disruption of cell adhesion in HHD and DD.…”
mentioning
confidence: 99%
“…Although it is possible that reattaehment of cells occurs at higher levels, no evidence of such is apparent. Sato et al (1977) associated attachment plaques without tonofilaments between cells with cellular reattachment. Since adjacent epithelial mucosa appears normal, it is possible that cells from this mucosa migrated above the acantholytic area.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…Such changes as nuclear pyknosis and cytoplasmic vacuolation of the spiny layer cells as described by Gottlieb & Lutzner (1973) and Mann & Haye (1970) were not seen in our lesions at LM or EM levels. Sato et al (1977Sato et al ( , 1978 investigated earlier reports of accelerated cell renewal in Darier's disease. They used electron microscopic and light mictoscopic autoradiographic (H-' thymidinc) methods and concluded that there is an increased cell turnover rate as well as precocious keratin formation in skin.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%